IDNLearn.com offers a unique blend of expert answers and community-driven knowledge. Join our interactive community and get comprehensive, reliable answers to all your questions.

Solve by completing the square. Show all the work you use to arrive at your answer.

[tex]x^2 + 6x = 81[/tex]


Sagot :

Let's solve the equation [tex]\( x^2 + 6x = 81 \)[/tex] by completing the square. Here's a step-by-step walkthrough:

### Step 1: Move the constant term to the left side
First, let's rewrite the equation so that we have all the terms involving [tex]\( x \)[/tex] on one side and the constants on the other side:
[tex]\[ x^2 + 6x - 81 = 0 \][/tex]

### Step 2: Bring the constant term to the right side
Rewrite the equation to isolate the terms involving [tex]\( x \)[/tex] on the left side:
[tex]\[ x^2 + 6x = 81 \][/tex]

### Step 3: Add and subtract the square of half the coefficient of [tex]\( x \)[/tex]
To complete the square, we need to add and subtract the square of half the coefficient of [tex]\( x \)[/tex]. The coefficient of [tex]\( x \)[/tex] is 6, half of it is 3, and its square is 9. So, add and subtract 9 on the left side:
[tex]\[ x^2 + 6x + 9 - 9 = 81 \][/tex]
[tex]\[ x^2 + 6x + 9 = 81 + 9 \][/tex]

### Step 4: Factor the left-hand side
The left-hand side of the equation, [tex]\( x^2 + 6x + 9 \)[/tex], can be factored as a perfect square trinomial:
[tex]\[ (x + 3)^2 = 90 \][/tex]

### Step 5: Solve for [tex]\( x \)[/tex]
Now, we have the equation in the form of a perfect square:
[tex]\[ (x + 3)^2 = 90 \][/tex]

To find the values of [tex]\( x \)[/tex], take the square root of both sides:
[tex]\[ x + 3 = \pm \sqrt{90} \][/tex]

Thus, we get two solutions:
[tex]\[ x + 3 = \sqrt{90} \quad \text{and} \quad x + 3 = -\sqrt{90} \][/tex]

Simplify the square root of 90:
[tex]\[ \sqrt{90} = 3\sqrt{10} \][/tex]

So, the solutions are:
[tex]\[ x + 3 = 3\sqrt{10} \quad \Rightarrow \quad x = 3\sqrt{10} - 3 \][/tex]
[tex]\[ x + 3 = -3\sqrt{10} \quad \Rightarrow \quad x = -3\sqrt{10} - 3 \][/tex]

### Final Solutions
Therefore, the solutions to the equation [tex]\( x^2 + 6x = 81 \)[/tex] by completing the square are:
[tex]\[ x = 3\sqrt{10} - 3 \quad \text{and} \quad x = -3\sqrt{10} - 3 \][/tex]